The Importance Of Gaziantep City Economy For The Middle East - (:unkn) unknown (HALE SIVGIN, 2016)
During centuries Gaziantep has hosted many civilizations being one of the most important industrial and trade center in Turkey. Endowed with its trade potential and entrepreneurial spirit it easily integrated in the international markets. Strengthening its trade and economic ties with neighboring countries it evolved in important regional industrial and trade hub. By developing trade ties with the neighboring countries Gaziantep also provides important spillovers to the other municipalities and regions of Turkey. As the most developed city in the region Gaziantep is crucial gate to the markets of the Middle East. Enhancing economic relationships with the Middle Eastern countries it had important implications on speeding the economic development. It is also a mediator in commodity transfer between Western and Eastern countries. Continuous movements and war conflicts in the region had destructive effects on economic environment. During the periods of intense war conflicts the economy of Gaziantep is being seriously disbalanced and hit by recession cycles. However, inspite of these negativities Gaziantep is continuing with decreasing its export share to the Middle East countries. In this paper a general literature regarding the city of Gaziantep is being consulted along with the help of table and graphical tools in the analysis of the advantages and disadvantages, also in the same time economic importance of the Gaziantep for Turkey and Middle East region as well is being stressed and some suggestions are being explored in th concluding part.
Keywords: Gaziantep; Gaziantep economy; Gaziantep industry; Gaziantep export; Middle East